Band gap narrowing of TiO2 nanoparticles: A passivated Co-doping approach for enhanced photocatalytic activity. (March 2022) - Na-Phattalung, Sutassana; Harding, David J.; Pattanasattayavong, Pichaya; Kim, Heungsik; Lee, Jihye; Hwang, Dae-Woong; Chung, Taek Dong; Yu, Jaejun
Abstract: In anatase TiO2, various passivated co-dopants such as (V–N), (Mo–C), (Nb–N), (Ta–N), and (F–N) are of significant interest due to their enhanced photocatalytic activities under visible light. Unlike the bulk phase, the effect of co-dopants in TiO2 nanoparticles still lacks fundamental exploration. To understand this, we perform density-functional-theory calculations within the PBE generalized gradient approximation with corrections for the on-site Coulomb interaction (PBE + U ) as well as hybrid functional (HSE06) approaches to investigate potential co-doping species and their locations in TiO2 nanoparticles that could be suitable for applications as antibacterial agents or for the degradation of organic pollutants. To allow an effective comparison with experiments, the criteria are set based on the experimentally measured band edge positions of TiO2 nanoparticles and the redox potentials of the reactive oxygen species of interest. Based on the analysis of donor and acceptor levels derived from thirty co-dopants, we find that the vanadium-nitrogen (VTi –NO ) pair in the T2 configuration is the most suitable passivated co-dopant for enhanced photocatalytic activity as it can reduce the band gap of TiO2 nanoparticles while still providing a thermodynamic driving force for redox reactions to generate reactive oxygen species. Graphical abstract: Image 1 Highlights: 30 passivated co-doping pairs in TiO2 nanoparticles (NPs) were investigated. Selection criteria were based on experimental data of band edges and redox potentials. (VTi –NO ) is the most suitable for enhancing photocatalytic activity of TiO2 NPs. (VTi –NO ) increases visible light absorption without creating recombination centers.